Description of two new species of Palpomyia Meigen (Diptera: Ceratopogonidae) from the Brazilian Amazon - Almeida, Jessica Feijó; Farias, Emanuelle de Sousa; Alencar, Ronildo Baiatone; Pessoa, Felipe Arley Costa (EntomoBrasilis, 2017)
Resumo. Duas novas espécies de insetos predadores e bioindicadores da qualidade da água do gênero Palpomyia, grupo distincta, são descritas e ilustradas baseadas em espécimes machos. Os imaturos das espécies Palpomyia amazonensis sp. nov. e Palpomyia lanceolata sp. nov. foram coletados em armadilhas ovitrampas e criados em laboratório até adultos. Ambas novas espécies são semelhantes a Palpomyia guyana Clastrier, 1992 e Palpomyia turnbowi Grogan et al., 2013 e diferem de Palpomyia versicolor Macfie, 1939, única espécie do grupo distincta descrita na Amazônia Brasileira. Com as duas descrições, foram aumentadas para três o número de espécies para a Amazônia e 32 para o Brasil. Descrição de duas novas espécies de Palpomyia Meigen (Diptera: Ceratopogonidae) da Amazônia brasileira Abstract. Two new Amazonian predaceous midge of the genus Palpomyia, from the distincta group, were described based on male specimens. This genus is an important bioindicator of aquatic environments. The immatures of Palpomyia amazonensis sp. nov. and Palpomyia lanceolata sp. nov. were collected with ovitraps and reared in laboratory until adulthood. Both new species are similar with Palpomyia guyana Clastrier, 1992 and Palpomyia turnbowi Grogan et al., 2013 but differs from Palpomyia versicolor Macfie, 1939, the unique species described in Brazilian Amazon until now. With the description of these new species we increase to three the representative species of the distincta group in the Brazilian Amazon and to 32 the number of Brazilian species of Palpomyia.